2018
DOI: 10.1016/j.athoracsur.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Is Predictive of 1-Year Mortality After Transcatheter Aortic Valve Replacement

Abstract: Most of the commonly used pre-TAVR risk assessments are poorly predictive of 1-year mortality. Albumin was the only frailty marker that was associated with higher mortality. Future studies should investigate whether optimization of nutritional status can improve outcomes after TAVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 24 publications
(39 reference statements)
0
24
1
Order By: Relevance
“…Hebeler, et al reported that the STS score alone was poorly predictive of IMPACT OF SERUM ALBUMIN ON TAVR one-year mortality after TAVR, and albumin was the only frailty marker associated with higher mortality. 44) Hypoalbuminemia's likely relation to mortality in the TAVR population may be explained by various reasons. Albumin is commonly correlated with more severe comorbidities, such as malignancy (sometimes occult), acute or chronic infective diseases, nutritional status, diabetes mellitus, and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Hebeler, et al reported that the STS score alone was poorly predictive of IMPACT OF SERUM ALBUMIN ON TAVR one-year mortality after TAVR, and albumin was the only frailty marker associated with higher mortality. 44) Hypoalbuminemia's likely relation to mortality in the TAVR population may be explained by various reasons. Albumin is commonly correlated with more severe comorbidities, such as malignancy (sometimes occult), acute or chronic infective diseases, nutritional status, diabetes mellitus, and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty, as defined in previous works, refers to patients with inpatient hypoalbuminemia and muscle weakness/fatigue. 18 Patients with diagnosis of infection, inflammatory spondyloarthropathies, neoplasm, pathologic or traumatic fractures, history of trauma or pregnancy were excluded from the study.…”
Section: Definition Of Casesmentioning
confidence: 99%
“…Since the last century, physicians have linked hypoalbuminemia to the increase of mortality and morbidities [22]. New evidence has continuously emerged to indicate the important role that hypoalbuminemia can play in making accurate diagnosis and implementing effective treatment for critically ill patients [23,24,25,26]. Today, it seems to have reached a consensus among physicians that providing exogenous albumin to critically ill patients can lead to increased survival rate.…”
Section: Discussionmentioning
confidence: 99%